Angular momentum in jumps with rotations on the longitudinal axis in figure skating - 3D-analyses and computer simulation - Knoll, Ka.; Hildebrand, F. (1997)
We study practical applications in sports to present conclusions for the training of sports technique. We give recommendations for individual solutions concerning sports technique res. present general models to optimise sports technique of the most complicated technical elements. Using the example of the triple Axel, the most complicated triple jump in figure skating, we present opportunities for an interpretation of our results in sports practice. In another procedure we can illustrate contribution of the individual parts an the body on the production of total angular momentum. Thus we present special information on different reasons for tilting the longitudinal axis to coaches and skaters.